Validation of the Chinese Version of Relaxation Sensitivity Index: A Tool for Predicting Treatment Effect in Mindfulness Interventions - Jieting Zhang; Jieting Zhang; Christina M. Luberto; Qi Huang; Jin Kuang; Juan Zhong; Albert Yeung; Liye Zou; Liye Zou (Frontiers Media S.A., 2021)
Background: The Relaxation Sensitivity Index (RSI) measures relaxation-related fears developed and validated in western samples. The RSI captures three facets of fear regarding relaxation: physical, cognitive, and social concerns. This study aimed to translate and identify the factor structure of the Chinese version of the RSI.Methods: In a preliminary study, 26 items were generated mainly by translation and modified from the original RSI. In Study 1, factor analysis and internal consistency reliability analysis were conducted on separated half samples of 597 Chinese college students. In Study 2, test-retest reliability, convergent, and predictive criterion validity were examined based on 465 Chinese college students.Results: Fourteen items were selected based on the factor loading and item prevalence in the preliminary study. Factor analysis based on Study 1 identified three factors: Social appealing, Social performance, and Physical concerns. In general, the RSI demonstrated good internal consistency (αs = 0.750-0.860), convergent validity and predictive criterion validity, while the test-retest reliability is relatively low (rs = 0.525-0.685). Notably, less related to the other two factors, Social performance concerns may be a unique factor solely predicting social anxiety (p <0.001), but not relaxation-induced anxiety (p = 0.442).Conclusion: The Chinese version of the RSI possesses a factor structure different from the western population. The robustness of factor structure and test-retest reliability was not as good as expected. Further research is warranted to explore the validity of the RSI in Chinese samples.